[Cocoa] - (:unkn) unknown (My University, 2009)
Labourers working on a pile of cocoa pods, splitting the pods to extract the cocoa beans.
Colour: Black and White; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cocoa trade--Trinidad and Tobago; Agriculture--Trinidad and Tobago; Agricultural laborers--Trinidad and Tobago; Employees--Trinidad and Tobago; Cacao--Trinidad and Tobago